The Implementation of Inclusive Education Programs in Reading Practice for Low-Grade Slow Learners in Elementary Schools - Hidayah, Refiana; Utami, Ratnasari Diah (Jurnal Elementaria Edukasia, 2024)
Education is a fundamental entitlement granted to children, aimed at preparing forthcoming generations. However, it's imperative to acknowledge that not all children grasp education at the same pace, often referred to as slow learners. Additionally, the lack of specialized mentorship in primary schools exacerbates this issue. Therefore, it's crucial for teachers to employ effective strategies to address these challenges. This study seeks to outline the utilization of an approach method in supplementary reading sessions tailored for slow learners. Employing a descriptive qualitative research design, data was gathered through observations, in-depth interviews, and document analysis. The research, structured as an intrinsic case study, involved two class teachers and slow learner students in grades one and two at SDN Wiropaten. Data analysis comprised data reduction, display, and inference drawing, with data validity ensured through source and technique triangulation, along with crosschecking. Findings indicate the effectiveness of the approach method in catering to the needs of slow learner students in lower grades. Several programs and outcomes stemming from this approach were identified. Grade one initiatives encompassed building rapport with slow learners, fostering trust, facilitating social interaction, and implementing follow-up strategies. Grade two initiatives included assigning independent tasks, engaging in random student participation (such as alphabet memorization), word games, and guided reading exercises.